Community policing: comparative aspects of community oriented police work - Dölling, Dieter; Feltes, Thomas (Empirische Polizeiforschung, 1993)
In the early 1980's, the outlines of a new direction for policing, know as "community policing", began to emerge and take root throughout the United States and many other countries. Since then interest in community policing has grown rapidly and police in many jurisdictions have developed and implemented some form of community policing. Officers were freed to engage in proactive crime prevention. Police operations were more visible, increasing police accountability to the public. Operations were decentralized to meet the needs of various neighborhoods and constituencies. Citizens were encouraged to take more initiative in preventing crimes and became partners with police, improving relations between the police and the public. Evidence from field experiments tested the theory that closer ties between the police and the citizens of the community, raise levels of citizen satisfaction with police services, improve the quality of community life, and lower the levels of fear of crime. The articles in this book were put together after a symposium on the occassion of the 30th anniverary of the Institute of Criminology at the University of Heidelberg. The idea was to summarize and to actualize the discussion on the concept of Community Policing and to consider the actual situation in some Eastern European countries.